Targeted Treatments of Bone Metastases in Patients with Lung Cancer - Hirsh, Vera (Frontiers in Oncology, 2014)
Until now approximately 30-40% of patients with advanced lung cancer develop bone metastases, but as the newer therapies are extending survival, the chance of developing bone metastases increases.Bone metastases cause skeletal-related events (SREs) such as pathologic fractures, spinal cord compression, radiation therapy or surgery to bone or hypercalcemia which can have debilitating consequences affecting patients' health-related quality of life (HR QOL) and performance status (PS). Poor PS then prevents the patients to receive further lines of treatments which are available today. SREs are associated with increased economic costs. In one clinical trial, the median time to first SRE was only 5 months. Early detection of bone metastases can prevent SREs and avoid inappropriate implementation of major surgery or chemoradiation therapy. With the new generation bisphosphonate zoledronic acid or denosumab (anti-RANKL activity), one can reduce the number of patients who experience SREs, decrease the annual incidence of SREs and delay the median time to first SRE. These agents are effective even after the onset of SREs. They are well tolerated, with manageable side effects. The biochemical markers of bone metabolism especially N-telopeptide of type I collagen (NTX) and bone specific alkaline phosphatase (BALP) can be both prognostic and predictive markers for the patients with bone metastases from NSCLC. Anticancer activity of zoledronic acid and denosumab further supports their use as soon as bone metastases are diagnosed in patients with non-small cell lung cancer (NSCLC). Further trials will inform us about the efficacy of these agents for prevention of bone metastases and even about possible effects on visceral metastases.